Collaborative Writing in EFL Settings: A Review - Pardede, Parlindungan (JET (Journal of English Teaching), 2024)
Despite the use of various approaches in writing classes, writing is still the most difficult language skill to master for most ESL/EFL learners. To overcome the problem, collaborative writing has been recommended since the 1970's. Since this approach involves learners in the activities of understanding, manipulating, producing, and interacting which facilitates them not only to practice writing, it is believed to be effective in helping the learners become better writers. This article reviews related publications on collaborative writing to provide insights and recent developments in collaborative writing implementation in EFL settings. Research on its implementation in ESL settings does reveal its effectiveness in improving learners' writing skills. However, due to linguistic experience and socio-cultural background differences between ESL and EFL learners, what works effectively in ESL does not automatically work well in EFL. To implement collaborative writing fruitfully in their EFL classes, teachers need to provide a conducive and supportive learning environment and effective guidelines for the entire writing process.